A Robust Switchable Oil‐In‐Water Emulsion Stabilized by Electrostatic Repulsions between Surfactant and Similarly Charged Carbon Dots. Issue 11 (29th December 2022) - Abbas, Ansar; Zhang, Chen; Hussain, Sameer; Li, Yang; Gao, Ruixia; Li, Jing; Liu, Xueyi; Zhang, Minghui; Xu, Silong
Abstract: How to control the stability of oil‐in‐water (O/W) emulsions is one of the main topics for scientists working in colloidal systems. Recently, carbon dots (CDs) have received great interest as smart materials because of their excellent physicochemical properties and versatile applications. Herein, for the first time, advanced and switchable O/W emulsions are presented that are stabilized by the synergistic effect of cationic surfactant cetyltrimethylammonium bromide CTAB (emulsifier) and similarly charged CDs (stabilizer). In the formulated emulsion, the cationic surfactant molecules are adsorbed at the oil and water interface to decrease the interfacial tension and enrich the drops with a positive charge to ensure intensive electrostatic repulsions among them. On the contrary, cationic CDs are distributed in the water phase among the droplets to reduce the water secretion and prevent flocculation and droplet coalescence. The stabilizing effect is found to be universal for emulsions of a range of oil phases. Furthermore, the formulated emulsion is found to be switchable between "stable" and "unstable" modes by adding an equivalent of anionic surfactant sodium dodecyl benzene sulphonate (SDBS). The stabilized and switchable O/W emulsions are believed to have wide practical applications in water purification, pharmaceuticals, protein recognition, as well as catalysis. Abstract : An advanced and switchable O/W emulsion is prepared and stabilized by synergistic effect of cationic surfactant and similarly charged carbon dots. The stabilizing effect is found to be universal for a range of oil phases and the formulated emulsion is switchable between "stable" and "unstable" modes by adding an equivalent amount of anionic surfactant SDBS.